If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8y + 6 = -9 + -7y Reorder the terms: 6 + -8y = -9 + -7y Solving 6 + -8y = -9 + -7y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '7y' to each side of the equation. 6 + -8y + 7y = -9 + -7y + 7y Combine like terms: -8y + 7y = -1y 6 + -1y = -9 + -7y + 7y Combine like terms: -7y + 7y = 0 6 + -1y = -9 + 0 6 + -1y = -9 Add '-6' to each side of the equation. 6 + -6 + -1y = -9 + -6 Combine like terms: 6 + -6 = 0 0 + -1y = -9 + -6 -1y = -9 + -6 Combine like terms: -9 + -6 = -15 -1y = -15 Divide each side by '-1'. y = 15 Simplifying y = 15
| x-48=6 | | 5(x+2)-(5x+10)=0 | | 4x+2=10x-1 | | 80*6x=45+32*4x+23x | | (3x+1)(2x-4)-x(6x-7)=0 | | 32=48t+16t^2 | | .25(16x-20)=.5(10x-8) | | 6y-2x=24 | | 5t+5=-2-7t | | 5y-2y=21 | | 15x^2+2x-56=0 | | 4p+5q= | | 8d=-4+12 | | 16(x-64)=32 | | 5k+6=15 | | x^6-12x^4+48x^2-60=0 | | 53x+56/26-69*(85*4)=5 | | 5+2b=10-3b | | 7x+8=64 | | 98-7x=11x+24 | | 12-5*(5-4x)=27 | | 115-6x=30x+23 | | 4p-3=7 | | 6y+3x=24 | | 54-4x=5x+20 | | 8x-3=2c+15 | | x(3x+11)=4 | | 14-10x=142-38x | | 7-7x=207-42x | | 6x+9=-135-10x | | 144-5x=6x-9 | | -19-3x=5-9x |